Migration, personal physical safety and economic survival: drivers of risky sexual behaviour among rural-urban migrant street youth in Kampala, Uganda - Mulekya Francis Bwambale; Deborah Birungi; Cheryl A. Moyer; Paul Bukuluki; Bart van den Borne (BMC, 2022)
Abstract Background Despite the vulnerabilities associated with the youth migration process, knowledge on the drivers of risky sexual behaviour among migrant street youth is limited. This study sought to explore the pathways driving risky sexual behaviour among rural-urban migrant street youth in Kampala, Uganda. Methods We conducted 11 focus-group discussions composed of 8-10 participants each, and 15 in-depth interviews with urban street adolescents and youth aged 12-24 years. We purposively recruited street youth who had migrated from other districts to Kampala, Uganda, and who identified themselves as street youth. Data were analysed thematically using an inductive approach facilitated by Dedoose software. Results The migration journey acted as a catalyst for risky sexual behaviour among the adolescents and youth moving from rural districts to Kampala. Three primary pathways were found to drive risky sexual behaviour of street youth: 1) rural-urban migration itself, through sexual exploitation of and violence toward street youth especially young girls during movement, 2) economic survival through engaging in casual jobs and sex work upon arrival in the city, and 3) personal physical safety through friendships and networks, which consequently lead to having multiple sexual partners and unprotected sex. Engagement in risky sexual behaviour, especially sex work, was found to be an adaptation to the challenging and complex street life within the city. Conclusions This study highlights the migration process, personal physical safety and economic survival as major pathways driving risky sexual behaviour among rural-urban street youth in Kampala. Interventions to improve sexual health, physical safety and protection of street youth during the migration process and within the city spaces should be prioritised.